Adipogenesis of adipose-derived stem cells may be regulated via the cytoskeleton at physiological oxygen levels in vitro. - Schiller, Zachary A.; Schiele, Nathan R.; Sims, James K.; Lee, Kyongbum.; Kuo, Catherine K. (2016)
Introduction: Obesity, which is excessive expansion of white adipose tissue, is a major risk factor for several serious health issues, including diabetes, cardiovascular disease and cancer. Efforts to combat obesity and related diseases require understanding the basic biology of adipogenesis. However, in vitro studies do not result in lipid composition and morphology that are typically seen in vivo, likely because the in vitro conditions are not truly representative of in vivo adipose tissue formation. In vitro, low oxygen tension and cytoskeletal tension have been shown to independently regulate adipogenesis, but in vivo, these two factors simultaneously influence differentiation.; Keywords: Adipogenesis, Cytoskeleton, Oxygen tension, Adipose-derived stem cells.; Springer Open.